USER ACCEPTANCE OF ONLINE WAQF APPLICATIONS: EVIDENCE FROM INDONESIA - Faturohman, Taufik; Hassandi, Irfan; Yulianti, Yulianti (Journal of Islamic Monetary Economics and Finance, 2020)
Waqf is an Islamic asset endowment to be kept in faith and used for charitable or religious purposes. Its function is to demonstrate the potential and economic benefits of waqf assets for worship and other people’s prosperity. Indonesia has great opportunities to raise more significant amounts of waqf funds. One strategy that appears effective with regard to waqf, especially cash waqf, is to provide an online service. Hence, this research attempts to analyse whether the perceived usefulness, perceived ease of use, perceived religiosity, and amount of information influences user acceptance of using an online waqf application process by implementing  the technology acceptance model (TAM). Moreover, the study incorporates structural equation modelling (SEM) to interpret the path analysis of the model. The study fills the gap in the literature concerning the context of use of the technology acceptance model for online waqf in Indonesia. We find that the variables that directly influence user acceptance of online waqf application are perceived usefulness and perceived ease of use, with perceived ease of use influencing perceived usefulness. In addition, perceived ease of use is influenced by the amount of information. Furthermore, the majority of respondents prefer to have projects such as mosques, Islamic boarding schools, schools, and hospital construction projects. To increase user acceptance, online waqf developers should provide more information about the application process and develop more user-friendly software with many features. Moreover, regulators should provide incentives for online waqf developers to maximise cash waqf collection.